Neuronal Nitric Oxide Synthase Knockdown Within Basolateral Amygdala Induces Autistic-Related Phenotypes and Decreases Excitatory Synaptic Transmission in Mice - Wang, Xiaona; Gao, Chao; Zhang, Yaodong; Xu, Jinxiu; Fang, Quanfeng; Gou, Lingshan; Yang, Zhigang; Mei, Daoqi; Liu, Leiming; Li, Linfei; Liu, Jing; Zhang, Huichun; et al. (Frontiers in Neuroscience, 2020)
Autism spectrum disorder (ASD) is a heterogeneous group of neurodevelopmental disorder characterized by deficits in communication, impaired social interaction, and repetitive or restricted interests and behaviors. We have recently shown that neuronal nitric oxide synthase (nNOS) expression was reduced in the basolateral amygdala (BLA) of mice following postnatal valproic acid (VPA) exposure. However, the specific role of nNOS down-regulation in mice remains to be elucidated. Herein, we investigated the behavioral alternations of naive mice with a recombinant adeno-associated virus (rAAV)-mediated knockdown of nNOS in a comprehensive test battery including the social interaction, marble burying, self-grooming and open field tests. Further, the electrophysiological and surface expression changes induced by nNOS deficiency of the BLA in these animals were examined. Our results show that nNOS knockdown displayed typical symptoms of ASD-like behaviors, such as reduced social interaction and communication, elevated stereotypes and anxiety in mice. Surprisingly, we found that nNOS knockdown exhibited greatly reduced excitatory synaptic transmission concomitant with the lower surface expression of GluN2B-containing NMDA receptors and postsynaptic density (PSD95) in mice. These findings support a notion that dysregulation of nNOS might contribute to ASD-associated phenotypes, with disease pathogenesis most likely resulting from deficits in excitatory synaptic transmission.